Entre vozes e ecos da floresta, da Terra e do Eware: da epifania do mistério às pujanças do ritual Ticuna no Alto Solimões, Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The texture of this thesis brings the result of the research carried out in the community Ticuna of Vendaval, in the indigenous lands of Eware II, a place belonging to the municipality of São Paulo de Olivença and located in Alto Solimões, Amazonas. The study thematizes the voices and echoes of the forest, the land and the Eware, the sanctuary of the origins and Magüta cultural traditions and those of their Ticuna descendants (the Land of their ancestors). Focuses on, in this context, on the epiphany of mystery to the “pujanças” of the Ticuna ritual in Alto Solimões. To this end, the studies aimed to investigate how the epiphany of enigmas relates to cosmology and how its myths influence and present themselves in the life, in discourses, in daily life of the Ticuna people of the indigenous community of Vendaval and in the border context. This is a qualitative investigation with a focus and ethnographic approximation, a process that, in a particularized way, opportunised to approach of the social subjects in order to obtain empirical data. These were collected through observation, seek, conversations, narrated memories and perceptions of the Ticuna way of life in different places in the community and in other spaces. Therefore, it dealt with human beings and, as far as subjective aspects are concerned, their feelings, beliefs, spirituality. Living with these people helped to better understand the facts of the core of the culture, which was sought to elucidate with the contribution of ten social subjects Ticuna and two non-indigenous. Thus, totaled twelve subjects with their specialties of acting and function. The dialogues and discussions in all trajectories of experiences with the original Ticuna people in the various contexts of investigations and coexistence, gave more certainty of the importance of the ancestral knowledge of the mythical and traditional universe from the perspective of the reflective gaze of subjects in the contemporary world and in Amazonian border.
Between voices and echoes of the forest, Earth and Eware: from the epiphany of the mystery to the strengths of the Ticuna ritual in Alto Solimões, Amazonas
Keywords: Índios Ticuna - Rituais; Indígenas - Usos e costumes; CIENCIAS HUMANAS; Floresta Amazônica; Mitos tradicionais; Epifania do mistério; Ritual Ticuna; Ticuna